1998
DOI: 10.1289/ehp.98106787
|View full text |Cite
|
Sign up to set email alerts
|

Children's health and the environment: a new agenda for prevention research.

Abstract: Patterns of illness in American children have changed dramatically in this century. The ancient infectious diseases have largely been controlled. The major diseases confronting children now are chronic and disabling conditions termed the "new pediatric morbidity" asthma mortality has doubled; leukemia and brain cancer have increased in incidence; neurodevelopmental dysfunction is widespread; hypospadias incidence has doubled. Chemical toxicants in the environment as well as poverty, racism, and inequitable acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 46 publications
2
61
0
4
Order By: Relevance
“…In the assessment of the effects of exposure to toxic chemicals such as MIC; the age, sex of the subject, physiological and nutritional statuses, as well as other confounding factors, have to be taken into account [69,70]. There is a compelling need for detailed investigations into the health implications of children's exposure to environmental toxins, with special reference to the high prevalence conditions, such as childhood cancer, asthma, endocrine and sexual disorders, and neurobehavioral toxicants [71]. Anthropometric studies in adolescents carried out by Ranjan et al [72] identified selective growth retardation in boys either exposed to the toxic MIC gas as toddlers or born to the exposed patients but not in girls.…”
Section: Molecular Studies With Reference To Micmentioning
confidence: 99%
“…In the assessment of the effects of exposure to toxic chemicals such as MIC; the age, sex of the subject, physiological and nutritional statuses, as well as other confounding factors, have to be taken into account [69,70]. There is a compelling need for detailed investigations into the health implications of children's exposure to environmental toxins, with special reference to the high prevalence conditions, such as childhood cancer, asthma, endocrine and sexual disorders, and neurobehavioral toxicants [71]. Anthropometric studies in adolescents carried out by Ranjan et al [72] identified selective growth retardation in boys either exposed to the toxic MIC gas as toddlers or born to the exposed patients but not in girls.…”
Section: Molecular Studies With Reference To Micmentioning
confidence: 99%
“…Their tissues directly absorb these substances, and -due to their immaturity-they are not able to restore the damages caused. So, if their brain, immune, or endocrine system are affected by toxic substances, the damage caused can be permanent and irreversible (Landrigan et al, 1998). Data relate the development of leukemia in children living in areas with high concentrations of suspended particles.…”
Section: Air Pollution Health and Environmental Injusticementioning
confidence: 99%
“…Infant mortality has declined sharply. The predominant diseases of children have now become the suite of chronic illnesses termed the "new pediatric morbidity"-asthma, learning disabilities, congenital malformations, and cancerthat are also the leading causes of morbidity and mortality for children in Western Europe and North America (Landrigan et al 1998).…”
Section: Industralization and Urbanization Of Southeast Asia And The mentioning
confidence: 99%
“…Children are especially at risk of exposure to the approximately 15,000 high-production-volume chemicals that are produced in largest quantities worldwide and that have the potential to be most widely disseminated in the environment, nearly all of them developed in the past 50 years. These chemicals include such neurotoxic substances as lead, solvents, mercury, pesticides, and polychlorinated biphenyls (PCBs) (Landrigan et al 1998). Fewer than half of these highproduction-volume chemicals have been tested for their potential toxicity, and fewer still for their possible developmental toxicity to fetuses, infants, and children (National Academy of Sciences 1984; U.S. EPA 1998).…”
Section: Industralization and Urbanization Of Southeast Asia And The mentioning
confidence: 99%